Photosensitised Multiheme Cytochromes as Light‐Driven Molecular Wires and Resistors. (13th September 2018) - van Wonderen, Jessica H.; Li, Daobo; Piper, Samuel E. H.; Lau, Cheuk Y.; Jenner, Leon P.; Hall, Christopher R.; Clarke, Thomas A.; Watmough, Nicholas J.; Butt, Julea N.
Abstract: Multiheme cytochromes possess closely packed redox‐active hemes arranged as chains spanning the tertiary structure. Here we describe five variants of a representative multiheme cytochrome engineered as biohybrid phototransducers for converting light into electricity. Each variant possesses a single Cys sulfhydryl group near a terminus of the heme chain, and this was efficiently labelled with a Ru II (2, 2′‐bipyridine)3 photosensitiser. When irradiated in the presence of a sacrificial electron donor (SED) the proteins exhibited different types of behaviour. Certain proteins were rapidly and fully reduced. Other proteins were rapidly semi‐reduced but resisted complete photoreduction. These findings reveal that photosensitised multiheme cytochromes can be engineered to act as resistors, with intrinsic regulation of light‐driven electron accumulation, and also as molecular wires with essentially unhindered photoreduction. It is proposed that the observed behaviour arises from interplay between the site of electron injection and the distribution of heme reduction potentials along the heme chain. Abstract : Biohybrid phototransducers of visible light to electricity. We produced tetraheme cytochromes photosensitised by attachment of a Ru II dye. The site of Ru II labelling defined whether the resulting bihybrids acted as molecular wires or resistors when irradiated in the presence of a sacrificial electron donor (SED).